2013
DOI: 10.5127/jep.029112
|View full text |Cite
|
Sign up to set email alerts
|

State Rumination: Associations with Emotional Stress Reactivity and Attention Biases

Abstract: Within dysphoria, rumination has been identified as a particularly maladaptive emotion regulation strategy linked to prolonged negative affect and the onset of depressive episodes. Until now, the majority of research assessing naturally occurring rumination has utilized trait rumination measures; however, additional information may be obtained by assessing state rumination. The current study examined the association between state rumination and participants’ emotional recovery from stress. In addition, biased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
49
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 54 publications
2
49
1
Order By: Relevance
“…These findings are consistent with findings from other recent studies demonstrating cognitive control difficulties for positive and negative emotional information among ruminators (e.g., Joormann & Tran, 2009; see Whitmer & Gotlib, 2012, for a review). For example, our findings are consistent with a study that found poststressor rumination was associated with difficulty disengaging from sad, angry, and happy faces among dysphoric individuals on an exogenous cuing task (LeMoult, Arditte, D’Avanzato, & Joormann, 2013). The present findings are also consistent with another dot-probe study with youth that found greater attention to emotional faces associated with rumination among maltreated children following a sad mood induction (Romens & Pollak, 2012).…”
Section: Discussionsupporting
confidence: 91%
“…These findings are consistent with findings from other recent studies demonstrating cognitive control difficulties for positive and negative emotional information among ruminators (e.g., Joormann & Tran, 2009; see Whitmer & Gotlib, 2012, for a review). For example, our findings are consistent with a study that found poststressor rumination was associated with difficulty disengaging from sad, angry, and happy faces among dysphoric individuals on an exogenous cuing task (LeMoult, Arditte, D’Avanzato, & Joormann, 2013). The present findings are also consistent with another dot-probe study with youth that found greater attention to emotional faces associated with rumination among maltreated children following a sad mood induction (Romens & Pollak, 2012).…”
Section: Discussionsupporting
confidence: 91%
“…In keeping with this, meaningful differences between trait and state rumination have been reported. For instance, state rumination predicts subsequent negative affect, poor recovery from sad mood, and emotional reactivity to a social stressor, independently of trait rumination (Hilt, Aldao, & Fischer, 2015;LeMoult, Arditte, D'Avanzato, & Joormann, 2013;Moberly & Watkins, 2008). Taken together, these findings suggest that state rumination is a highly informative phenomenon for mental functioning, whose very features are not fully captured by trait rumination.…”
mentioning
confidence: 73%
“…However, a psychometrically sound measure that allows to assess fluctuations in state rumination has been lacking. Existing measures have so far focused on specific and narrow forms of state rumination or do not provide enough psychometric information to be deemed reliable, robust, and valid (e.g., LeMoult et al, 2013;Roberts et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, research has turned to the investigation of rumination more proximal to its occurrence using online reports (e.g., in diary studies, experience sampling studies). A great advantage of this shift in research paradigms is that rumination can be linked more directly to the occurrence of negative or stressful events (e.g., Genet & Siemer, 2012;LeMoult, 2013; see also Smith & Alloy, 2009). This way, rumination can be assessed as a more transient construct, namely a phenomenon that occurs within individuals, across time, and in relation to other time-varying phenomena (e.g., affect, stress).…”
mentioning
confidence: 99%